Enantiomeric Separation of Meclizine Hydrochloride in Pharmaceutical Dosage Form by HPLC Method - Gowramma, Byran; Kumar, Ramachandran S.; Kalirajan, Rajagopal; Lakshmanan, Kaviarasan; Meyyanathan, Subramanian Nainar (Current Drug Research Reviews, 2020)
Objective: A basic, powerful and isocratic chiral fluid chromatographic technique was created and approved for the enantiomeric partition of meclizine hydrochloride in pharmaceutical dose structure. Methods: The chromatographic partition was accomplished on Phenomenex® Lux Cellulose 1 (250 mm x 4.6 mm i.d, 5 μm molecule size) section utilizing portable stage framework containing acetonitrile: 25mM ammonium bicarbonate (75:25%v /v). The versatile stage was siphoned on the segment at the stream pace of 1.0 mL/min, and UV recognition was done at 230 nm. Result: The breaking points of recognition and measurement were observed to be 0.25 μg/mL and 1.00 μg/mL individually, for 20μL infusion volume. The alignment bend demonstrated phenomenal linearity over the focus scope of 1-5 μg/mL for (±) meclizine enantiomers with a relationship coefficient (r2 = 0.999). The recuperation investigation of meclizine from tablet plan was observed to be 97.33% and 98.81% separately. Meclizine standard arrangement and versatile stage were observed to be steady for in any event 32h. The meclizine enantiomers were very much settled with mean maintenance times of about (+) Meclizine at 13.14 min and (-) Meclizine at 14.33 min individually. Conclusion: The created technique was broadly approved and demonstrated to be hearty, exact, exact and appropriate for the examination of meclizine enantiomers in tablet measurement structure and security investigations of meclizine.
Keywords: enantiomers